Strategic entrepreneurship: entrepreneurial strategies for wealth creation - Hitt, Michael A.; Ireland, R. Duane; Camp, S. Michael; Sexton, Donald L. (Strategic Management Journal, 2001)
Abstract Entrepreneurship involves identifying and exploiting entrepreneurial opportunities. However, to create the most value entrepreneurial firms also need to act strategically. This calls for an integration of entrepreneurial and strategic thinking. We explore this strategic entrepreneurship in several important organizational domains to include external networks and alliances, resources and organizational learning, innovation and internationalization. The research in this special issue examines both traditional (e.g., contingency theory, strategic fit) and new theory (e.g., cultural entrepreneurship, business model drivers). The research also integrates, extends, and tests theory and research from entrepreneurship and strategic management in new ways such as creative destruction (discontinuities), resource‐based view, organizational learning, network theory, transaction costs and institutional theory. The research presented herein provides a basis for future research on strategic entrepreneurship for wealth creation. Copyright © 2001 John Wiley & Sons, Ltd.